Purification of polygalacturonases produced by Aspergillus niger using an aqueous two-phase system - Maciel, Marília de Holanda Cavalcanti (2014)
The partitioning and purification of polygalacturonases (PG) produced by Aspergillus niger URM 5162 were investigated in aqueous two-phase systems (ATPS), formed by polyethylene glycol and phosphate salts (PEG/phosphate). To evaluate the effect of the 4 independent variables – molar mass of polyethylene glycol (PEG) (400–8000 g/mol – MPEG), PEG concentration (12.5–17.5%, w/w – CPEG), phosphate concentration (15–25%, w/w, CPHOS) and pH (6.0–8.0) – on the 4 response variables: partition coefficient (K), activity yield (Y), purification factor (PF) and selectivity (S), a factorial design (24) was used. The endo-polygalacturonases (endo-PG) and exo-polygalacturonase (exo-PG) were preferentially partitioned in the top phase. For endo- and exo-PG, the highest values for the response variables K (1.23 and 2.40), Y (74.04% and 17.97%), PF (8.18 and 1.98) and S (24.68 and 48.07), respectively, were obtained for a CPEG of 12.5% (w/w), MPEG of 8000 g/mol, and CPHOS of 25% (w/w) at pH 6.0. These conditions were considered the most suitable for the purification of PG produced by A. niger URM 5162. Furthermore, the most important independent variables for endo- and exo-PG were CPHOS and MPEG, respectively. All independent variables studied and their interactions significantly influenced the response variables. According to these results, the PEG/phosphate system is a useful cost-effective alternative for purification of PG produced by A. niger URM 5162.